Diagnóstico da biodiversidade de vertebrados terrestres de Sergipe - Cordeiro, Juliana de Carvalho (2008)
This dissertation presents a diagnosis of the diversity of terrestrial vertebrates in the Brazilian state of Sergipe. Information on the general and regional distribution, conservation and expected occurrence of species were collected for each taxonomic group. The morphoclimatic domain model was adopted as the geographic baseline for the definition of the ranges of the 547 species identified. Most of the 45 species of amphibian expected for Sergipe are distributed throughout the different domains, although 11 are restricted to the Atlantic Forest. Two species of Phyllomedusa are endangered locally, almost all the 39 confirmed species are restricted to the Atlantic Forest. The 57 reptilian species are mostly widely-distributed lizards and snakes, although 11 are restricted to either the Atlantic Forest or the caatinga. Two species of nemidophorus lizards are endemic, and four have a local distribution, while approximately 30 of the expected species were confirmed. With regard to the 387 bird species, 14 are restricted to the Atlantic Forest and two to the caatinga. The albatross, Thalassarche melanophris, has a restricted distribution, and the passeriform Herpsilochmus pectoralis is on the list of endangered species. Approximately 450 species of birds 95 of which are endangered are expected to occur in Sergipe. Most of the 36 species of nonvolant mammals, plus the 22 bats, are from the Atlantic Forest and caatinga, or more amply distributed. Red-listed species include the Atlantic Forest bat Chiroderma doriae, the titi monkeys Callicebus coimbrai and C. barbarabrownae from the Atlantic Forest and caatinga, respectively, and the capuchin, Cebus xanthosternos. Of the 124 species that probably occur within the area, three are endemic to the caatinga, and four to the Atlantic Forest. The most important areas of the Atlantic Forest and caatinga for ecological studies and biological inventory are identified and discussed.